The self‐curing phenomenon of schistosome infection in rhesus macaques: insight from in vitro studies. Issue 1 (14th December 2017) - Torben, Workineh; Molehin, Adebayo J.; Blair, Robert V.; Kenway, Carys; Shiro, Faith; Roslyn, Davis; Chala, Bayissa; Gutu, Dereje; Kebede, Michael A.; Ahmad, Gul; Zhang, Weidong; Aye, Pyone; et al.
Abstract: A reduction in the burden of schistosomiasis is potentially achievable by integrating a schistosomiasis vaccine with current control measures. Here, we determine parasite‐specific in vitro responses of B, T, and NK cells from naive uninfected rhesus macaques to Schistosoma mansoni (Sm) egg (SmEA) and worm antigen (SmWA) preparations isolated from infected baboons. Pronounced B cell responses to SmEA and NK cell responses to both SmEA and SmWA were observed. High levels of IL‐2 and IL‐21 responses against Sm antigens were observed in T and non‐T cells of lymph nodes (LNs) and gut lamina propria–derived lymphocytes (LPLs). Data analysis showed multifunctionality of LN‐derived CD4 +, CD8 +, and CD4 + CD8 + double positive T cells against either SmWA or SmWA+SmEA antigen preparations. Distinct SmEA‐specific multifunctional responses were observed in gut LPLs, suggesting simultaneous responses against egg antigens. These data provide insight into the immune effectors involved in schistosome responses by rhesus macaques.